2021
DOI: 10.1177/0020731420981928
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization by Older Adults in Nepal: An Investigation of Correlates and Equity in Utilization

Abstract: This study aims to evaluate factors associated with health care utilization (HCU) and to assess vertical and horizontal equity in utilization among Nepali older adults. Data are from an existing cross-sectional study involving systematic random sampling of 260 older adults in Far-Western (Sudurpaschim) Province of Nepal. Andersen’s theoretical framework was used to assess predisposing, enabling, and need factors that have the potential to influence health care utilization. Multivariable logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…More monthly household income makes people more likely to use health services. Acharya et al [ 14 ], Gurung et al [ 4 ], Spaan et al [ 32 ], Babitsch et al [ 33 ], and Ghimire et al [ 34 ] also revealed an association among health service utilization, household income, and distance to the health facilities. It indicates that financial hardship is the greatest barrier to utilizing the health services among senior citizens.…”
Section: Discussionmentioning
confidence: 99%
“…More monthly household income makes people more likely to use health services. Acharya et al [ 14 ], Gurung et al [ 4 ], Spaan et al [ 32 ], Babitsch et al [ 33 ], and Ghimire et al [ 34 ] also revealed an association among health service utilization, household income, and distance to the health facilities. It indicates that financial hardship is the greatest barrier to utilizing the health services among senior citizens.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of quality health care's significance Advances in Public Health for older individuals is growing on a policy level, with governments worldwide initiating efforts to enhance the healthrelated quality of life for their older populations [77]. These initiatives include policies that subsidize health care for older persons, stimulating the demand for targeted and effective medical services tailored to their needs [78]. Increased government funding for research on age-related health issues has led to breakthroughs in understanding and treating ailments prevalent among older people [79].…”
Section: Social and Societalmentioning
confidence: 99%